AGE PECULIARITIES OF 8-ISOPROSTANE SERUM DYNAMICS IN EXPERIMENTAL CRANIO-SKELETAL TRAUMA - Sushko, Y.I.; Mykyta, О.O.; Hudyma, A.A.; Lisnychuk, N.E.; Denysiuk, Y.A.; Iavorska, I.V.; Liuta, O.O. (World of Medicine and Biology, 2024)
The main peculiarity of modern traumatism is the increasing frequency of severe combined and multiple trauma. Oxidative stress plays a leading role in the pathogenesis of secondary damage in cases of combined trauma. In experiments on rats of different age groups, the effect of combined skeletal and traumatic brain injury on the serum content of 8-isoprostane was studied on 1, 3, 7, 14, 21 and 28 days of post-traumatic period. It was found that modeling of cranio-skeletal trauma among rats of different age groups compared to control group is accompanied by a significant increase in the content of 8-isoprostane in the blood serum. Among immature rats, the index reaches a maximum in 7 days, significantly increases in other experimental groups and normalizes by the 28th day. In old rats, the greatest increase in the content of 8-isoprostane in the blood serum occurs after 3–21 days of the experiment; it is characterized by the lowest amplitude of growth with a further decrease by the 28th day, which does not reach the control level. In terms of the dynamics of 8-isoprostane content in the blood serum the group of mature rats occupies an intermediate position, which corresponds to the antioxidant and restorative capacity of rats of this age group.
Keywords: traumatic brain injury; femur fracture; age; oxidative stress; 8-isoprostane